Design of Electronic Medical Record System Based on Cloud Computing Technology - Pan Chuan Di (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
According to current status and problems of electronic medical records management system, it combines with the current the latest information technology, cloud computing, and it explores the solution of electronic medical records management system and puts forward the new ideas and methods; Based on the literature and information on cloud computing technology, we summarize the cloud computing theory, architecture, application model, etc. and select the appropriate application platform for the electronic medical records ; Based on the Google cloud computing technology , it focus on Google cloud computing platform Google App Engine and its solution Plan, it makes the research of collaborative electronic medical record system based on Google App Engine. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4392